Group-Based Compensation in Professional Service Firms: An Empirical Analysis of Medical Group Practices - Pizzini, Mina (The Accounting Review, 2010)
ABSTRACT: This study investigates factors influencing the use of group-based compensation in professional service partnerships and the relation between group-based compensation and performance. I use data on 11,971 physicians in 935 medical groups to expand the extant literature on group incentives by providing some of the first large-sample, empirical evidence on the role of task interdependence, income risk, mutual monitoring, and group size in a firm's choice of compensation contract. Consistent with agency theory, I find that group incentives are more prevalent in medical partnerships that practice highly task-interdependent specialties and those that face greater malpractice risk. Group-based incentives are also more common in relatively small groups in which homogeneity in training, experience, and gender facilitate mutual monitoring. Tests relating individual physician productivity to compensation method suggest that productive benefits induced by group incentives offset reductions in output associated with free-riding and effort devoted to monitoring.